Effects of synovial macrophages in osteoarthritis - Zhao, Kun; Ruan, Jiaqi; Nie, Liuyan; Ye, Xiangming; Li, Juebao (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a common degenerative disease in mammals. However, its pathogenesis remains unclear. Studies indicate that OA is not only an aging process that but also an inflammation-related disease. Synovitis is closely related to the progression of OA, and synovial macrophages are crucial participants in synovitis. Instead of being a homogeneous population, macrophages are polarized into M1 or M2 subtypes in OA synovial tissues. Polarization is highly associated with OA severity. However, the M1/M2 ratio cannot be the only factor in OA prognosis because intermediate stages of macrophages also exist. To better understand the mechanism of this heterogeneous disease, OA subtypes of synovial macrophages classified by gene expression were examined. Synovial macrophages do not act alone; they interact with surrounding cells such as synovial fibroblasts, osteoclasts, chondrocytes, lymphocytes and even adipose cells through a paracrine approach to exacerbate OA. Treatments targeting synovial macrophages and their polarization are effective in relieving pain and protecting cartilage during OA development. In this review, we describe how synovial macrophages and their different polarization states influence the progression of OA. We summarize the current knowledge of the interactions between macrophages and other joint cells and examine the current research on new medications targeting synovial macrophages.